Effects of Umbilical Cord Milking on Term Infants Delivered by Cesarean Section - Chiruvolu, Arpitha; Medders, Alexis; Daoud, Yahya (American Journal of Perinatology, 2020)
Objective Umbilical cord milking (UCM) is an efficient way to achieve optimal placental transfusion in term infants born by cesarean section (CS). However, it is not frequently performed due to concern for short-term adverse effects of increased blood volume, such as polycythemia and hyperbilirubinemia. The aim of this study is to evaluate the short-term effects of UCM on term infants delivered by CS.Study Design We conducted a pre- and postimplementation cohort study comparing term infants delivered by CS who received UCM five times (141 infants, UCM group) during a 6-month period (August 1, 2017 to January 31, 2018) to those who received immediate cord clamping (ICC) during the same time period (105 infants, postimplementation ICC) and during a 3-month period (October1, 2016 to December 31, 2016) prior to the implementation of UCM (141 infants, preimplementation ICC).Results Mothers were older in UCM group compared with both ICC groups. There were no significant differences in other maternal or neonatal characteristics. Although this study was not powered to detect differences in outcomes, the occurrence of hyperbilirubinemia needing phototherapy, symptomatic polycythemia, NICU admissions, or readmissions for phototherapy was similar between the groups.Conclusion UCM intervention was not associated with increased incidence of phototherapy or symptomatic polycythemia in term infants delivered by CS.
Keywords: term infants; cesarean section; umbilical cord milking; hyperbilirubinemia; phototherapy